Penyajian Musik Antar-antaran Pada Acara Pernikahan Di Desa Penanggoan Duren Kecamatan Tulung Selapan Kabupaten Ogan Komering Ilir - Sepdwiko, Deria (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
This study formulates the problem of how the form of music presentation in delivery at weddings in Penanggoan Duren Village, Tulung Selapan District, Ogan Komering Ilir Regency. This study aims to determine how the form of music presentation in, delivery at weddings in the village of Penanggoan Duren. This research is qualitative. Data collection techniques include observation, interviews, and documentation. The results showed that this delivery was only carried out when the bride and groom came from the same village, this was because the distance was far in the process of walking, and this delivery only used kenong and tambourine instruments as media accompaniment. intermediate. The wasp pattern in kenong has 1 pattern that is usually played, then the tambourine has a wasp pattern, namely wasps 1, 2, 3, and 4. The art of inter-delivery music which has become a basic need for the community of Penanggoan Duren village, Tulung Selapan sub-district, Ogan Komering Ilir district as a special media for accompaniment and entertainers who are always used in delivery at weddings. Inter-delivery is a traditional art in the village of Penanggoan Duren, which is a walking process carried out by the groom to the bride's house by bringing an offering to be given to the bride without a unilateral agreement. In the form of foodstuffs such as rice, chicken, spices, areca nut trees, bananas and many more.